Molecular epidemiology : principles and practices - Schulte, Paul A.; Perera, Frederica P. (Academic Press, 1993)
This groundbreaking work, now available in paperback, has helped to shape the emerging discipline of molecular epidemiology. Molecular Epidemiology has proven useful to epidemiologists unfamiliar with the terminology and techniques of molecular biology as well as to the molecular biologist working to understand the determinants of human disease and to use that information to control disease. This book demonstrates how molecular epidemiology utilizes the same paradigm as traditional epidemiology in addition to using biological markers to identify exposure, disease, or susceptibility.